Vyadhiksamatva In Ayurveda: The Fundamental Concept Of Immunity For A Healthy Life - Ravi, Dabas; Sweety, Sweety; A. C, Kar (Journal of Neonatal Surgery, 2026)
Vyādhikṣamatva is a fundamental concept of Ayurveda that denotes the inherent capacity of the body to resist disease and maintain physiological equilibrium. Unlike the modern biomedical understanding of immunity, which predominantly focuses on pathogen-specific defense mechanisms, Ayurveda conceptualizes immunity as a holistic, dynamic, and integrative phenomenon. It is governed by the balanced functioning of Doṣa, Dhātu, Mala, Agni, and Ojas, which together sustain health and vitality. In Ayurvedic literature, immunity is not viewed merely as a defensive response against external agents, but as an expression of overall systemic strength and adaptability.Classical Ayurvedic texts describe Vyādhikṣamatva as having a dual role: the prevention of disease manifestation and the capacity to counteract the intensity and progression of disease once it occurs. This approach highlights both preventive and curative dimensions of immunity. The maintenance of optimal digestive and metabolic activity through Agni is considered central to immune competence, as proper digestion leads to the formation of healthy tissues and prevents the accumulation of metabolic toxins. Ojas, regarded as the essence of all bodily tissues, is considered the substratum of strength, vitality, and resistance against disease.Further, factors such as Dhātu Bala (tissue strength), Prakṛti (constitutional makeup), dietary habits, lifestyle practices, and psychological well-being significantly influence Vyādhikṣamatva. Ayurveda emphasizes that mental disturbances such as stress, fear, and anger can impair immunity, whereas a balanced and positive mental state enhances resistance to disease. Rasāyana therapy, encompassing rejuvenative medicines and ethical conduct, plays a vital role in promoting longevity, strengthening immunity, and improving quality of life.In contemporary healthcare, where infectious diseases, lifestyle disorders, and stress-related illnesses are increasingly prevalent, the Ayurvedic concept of Vyādhikṣamatva offers a comprehensive framework for preventive and promotive health care. By focusing on strengthening the host rather than solely targeting pathogens, this classical concept supports an integrative approach that complements modern medical science and contributes to sustainable health management